In Vitro Study to Evaluate the Effect of Saliva Contamination on Microleakage of Composite Versus Two Kinds of Glass Ionomer Cement Restorations in Primary Teeth (Journal of Hama University, 2019)
Purpose: The aim of this study is to evaluate the effect of saliva contamination on microleakage around composite (Tetric N-ceram), glass ionomer (Fuji IX™) and glass ionomer (Medifil) in primary teeth.Materials and Methods: This in vitro study contained 90 intact newly extracted human primary teeth (canines and molars). The sample was divided randomly and equally into three groups according to restoration materials (composite Tetric N-ceram, glass ionomer Fuji IX™ and glass ionomer Medifil) and each group has been divided randomly and equally into two subgroups according to the existence of the saliva contamination (with and without saliva contamination).Result: The saliva contamination has caused an increase in the degree of microleakage in three types of restoration materials but this increase has been significant only in composite.Conclusion: The use of glass ionomer cement to restore primary teeth is better when it is difficult to control the saliva contamination, because the glass ionomer is less sensitive to saliva contamination than composite.